Transport of secretory and membrane glycoproteins from the rough endoplasmic reticulum to the Golgi. A rate-limiting step in protein maturation and secretion. - Harvey F. Lodish (1988)
Recent work indicates that transport of newly made secretory and membrane proteins from the rough endoplasmic reticulum (ER)' to the Golgi is a specific and highly regulated event.Different membrane and secreted proteins move from the ER to the Golgi at very different rates, and resident ER proteins do not move at all.Most integral membrane proteins and many secretory proteins undergo extensive covalent modifications and folding while still in the ER; recent studies suggest that proteins will not mature from the ER to the Golgi unless they have achieved a proper conformation.Finally, the nature of some of the signals on proteins that control their export from the ER is being elucidated by a combination of molecular, genetic, and biochemical dissection.However, the complexity and specificity of ER-to-Golgi transport is still not totally understood.